Increased Frequency of Giant Miniature End-Plate Potentials at the Neuromuscular Junction in Diabetic Rats - Julián Elías Martínez-Sánchez; Yolitzy Cárdenas; Xóchitl Trujillo; Mónica Ríos-Silva; M. Irene Díaz-Reval; Jaime Alberto Bricio-Barrios; Jesús Muñiz; Julio Alcaraz-Siqueiros; Miguel Huerta (Biomedicines, 2023)
There is a need for research addressing the functional characteristics of the motor end-plate in diabetes to identify mechanisms contributing to neuromuscular dysfunction. Here, we investigated the effect of diabetes on spontaneous acetylcholine release in the rat neuromuscular junction. We studied two randomized groups of male Wistar rats (n = 7 per group, 350 ± 50 g, 12–16 weeks of age): one with streptozotocin-induced experimental diabetes, and a healthy control group without diabetes. After 8 weeks of monitoring after diabetes induction, rats in both groups were anesthetized with pentobarbital. Then, the diaphragm muscle was dissected for electrophysiological recordings of miniature end-plate potentials (MEPPs) using a single electrode located at the region of the muscle end-plate. All experiments were conducted at environmental temperature (20–22 °C) in rat Ringer solution with constant bubbling carbogen (95% O2, 5% CO2). Compared to healthy controls, in the diaphragm neuromuscular end-plate derived from diabetic rats, the MEPPs were higher in amplitude and frequency, and the proportion of giant MEPPs was elevated (7.09% vs. 1.4% in controls). Our results showed that diabetes affected the acetylcholine MEPP pattern and increased the number of giant potentials compared to healthy controls.